The Role of Artificial Intelligence in Enhancing Critical Thinking in Education : A Systematic Literature Review - Rahmat Alvin Tarwanto; Yudianto Sujana; Nurcahya Pradana Taufik Prakisya (IJIE (Indonesian Journal of Informatics Education), 2025)
The emergence of generative AI, particularly language models like ChatGPT, has revolutionized educational practices by enhancing lesson planning and fostering critical thinking. This systematic literature review investigates the application of generative AI in creating effective lesson plans and its broader role in improving the educational process. By synthesizing findings from multiple studies, this research highlights AI's ability to personalize learning, provide adaptive feedback, and simulate real-world scenarios, which collectively promote analytical and reflective thinking among students. Additionally, the integration of ethical considerations in AI-supported education fosters responsible use and critical evaluation of AI systems. Despite its potential, challenges such as ethical dilemmas, dependency on technology, and algorithmic biases remain significant. This study underscores the transformative role of generative AI in modern education, offering practical insights and recommendations for integrating AI tools effectively. The findings contribute to understanding AI's impact on pedagogy, student engagement, and the development of higher-order thinking skills, emphasizing the importance of a balanced approach that aligns AI capabilities with human.